2020
DOI: 10.13111/2066-8201.2020.12.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Modelling of Unmanned Aerial System through Nonlinear Vortex Lattice Method, Computational Fluid Dynamics and Experimental Validation - Application to the UAS-S45 Bàlaam: Part 1.

Abstract: This paper describes a methodology to predict the aerodynamic behaviour of an Unmanned Aerial System. Aircraft design and flight dynamics modelling are mainly concerned with aerodynamics, and thus its estimation requires a high level of accuracy. The work presented here shows a new non-linear formulation of the classical Vortex Lattice Method and a comparison between this methodology and an experimental analysis. The new non-linear Vortex Lattice Method was performed by calculating the viscous forces from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Simulation results demonstrated that the proposed controller was able to properly estimate and compensate for the external disturbances to the UAS-S4 by guaranteeing more stable trajectory tracking. In addition, the UAS-S4 aerodynamic model was experimentally validated [31][32][33][34][35] at the LARCASE laboratory [36].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results demonstrated that the proposed controller was able to properly estimate and compensate for the external disturbances to the UAS-S4 by guaranteeing more stable trajectory tracking. In addition, the UAS-S4 aerodynamic model was experimentally validated [31][32][33][34][35] at the LARCASE laboratory [36].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies were applied on unmanned aerial systems (UAS). The LARCASE team developed sophisticated methodologies for predicting the aerodynamic behavior and performance of the unmanned aerial systems UAS-S4 and UAS-S45 of Hydra Technologies [22][23][24]. This work concentrated on the structural analysis and optimization of unmanned aerial systems UAS-S4 and UAS-S45 based on CFD optimization results (aerodynamic performance, viscous damping and oscillations) [25,26].…”
Section: Introductionmentioning
confidence: 99%